The effect of pH on cooperation between dark- and photo-fermentative bacteria in a co-culture process for hydrogen production from starch. (2nd February 2017) - Zagrodnik, R.; Łaniecki, M.
Abstract: The effect of pH control in biohydrogen production from starch by co-culture of dark fermentative Clostridium acetobutylicum and photofermentative Rhodobacter sphaeroides bacteria was studied. It was compared with hydrogen production rate and H2 yield obtained for single culture photo and dark fermentation. Development of stable bacteria co-culture resulted in complete decomposition of starch without accumulation of volatile fatty acids. Moreover, the amount of produced hydrogen was 2.5 fold higher than for single dark fermentation process, where maximum H2 production reached 0.939 L H2 /Lmedium at pH 5.5. Acclimatization of C. acetobutylicum to starch and control of pH at 7.0 was found optimum for bacteria cooperation in the co-culture, resulting in simultaneous H2 production by both bacteria species. Cumulative H2 production and H2 yield in this process reached 2.29 L H2 /Lmedium and 5.11 mol H2 /molglucose, respectively. Higher amounts of hydrogen (2.67 L H2 /Lmedium ) were obtained in a co-culture process in which pH was raised from 6.0 to 7.5 after dark fermentation stage. However, under these conditions dark and photofermentation stages were separated in time. Graphical abstract: Highlights: H2 production by co-culture of R. sphaeroides and C. acetobutylicum was studied. Starch from corn was applied as a complex carbon source. Activation of C. acetobutylicum on starch was crucial for the process at higher pH. Control of pH at 7.0 was the key issue for bacteria cooperation in the co-culture. No VFAs accumulation was observed at the end of the co-culture process.